INVESTIGATING THE PHOTOCATALYTIC DEGRADATION OF EMERGING PHARMACEUTICAL POLLUTANTS IN NIGERIAN SURFACE WATERS USING LOCALLY SOURCED CLAY-BASED NANOMATERIALS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The new drug pollutants in the surface waters are very harmful to the environment and health especially in developing countries such as Nigeria whereby the treatment of waste water is ineffective. This paper will analyze photocatalytic degradation of ibuprofen and ciprofloxacin in Nigerian surface water using iron-doped kaolinite nanomaterials produced using locally available clay. Anthropogenic contamination was observed in water samples of the Ogun River and Lagos Lagoon of the Lagos metropolis with a baseline ibuprofen concentration of 5.2-12.8 μg/L and a ciprofloxacin concentration of 3.1-9.4 μg/L. Wet impregnation was used to prepare iron-doped kaolinite photocatalysts, which was characterized through X-ray diffraction, scanning electron microscopy, Fourier-Transform infrared spectroscopy and Brunauer-Emmett-Teller analysis with an increase in surface area (45 m 2 /g) and a decrease in bandgap (2.8 eV). The degradation efficiencies of ibuprofen and ciprofloxacin were 92 and 85 percent under simulated solar irradiation in 120 minutes with the formation of hydroxyl radicals. The stability was also tested in terms of the reusability that showed the ability to sustain five cycles with a slow efficiency loss (less than 10 percent). The human health consequences of being exposed to the pollutants can be highlighted by the demographic statistics of the Lagos metropolis, which consists of a population of 17.1 million people, the majority of which are urban residents who are employed as traders and industrialists. Field sampling and laboratory tests were used to collect primary data, which combined the monitoring of the environment and the use of nanomaterials. Results indicate iron-doped kaolinite as the affordable and sustainable solution to water purification in resource-restricted environments, which is part of the global campaign against pharmaceutical pollution. The scaling in the future may reduce ecological effects in the contaminated Nigerian waterways.